ANTI-INFLAMMATORY EFFECTS OF AN AQUEOUS EXTRACT OF JUSTICIA FLAVA (FORSK) VAHL (ACANTHACEAE) IN RATS - WENCESLAS, KOUAME DJÈ KOUAMÉ; FRÉDÉRIC, N’DIA KOUADIO; LÉANDRE, KOUAKOU KOUAKOU; PAUL, YAPO ANGOUÉ (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Justicia flava is a plant commonly used in traditional medicine for the treatment of frictions, convulsions, body aches, pains, and fever. The aim of this study was to determine the anti-inflammatory properties of an aqueous extract of J. flava (AEJf) in rats. Methods: Thus, 36 rats were divided into six groups of six rats each for each test. Acute anti-inflammatory activity was evaluated by induction of plantar edema following injections of egg albumin, carrageenan, or histamine. AEJf and aspirin (100 mg/kg bw) were orally administered to rats with doses ranged from 62.5 to 500 mg/kg bw before (preventive study) and after (curative study) the induction of edema. The rat’s paw edema was measured using a digital caliper thereafter. For a sub-chronic anti-inflammatory activity, sterilized cotton pellets (20±0.5 mg) were implanted in the anterior dorsal region for granuloma formation. Animals received the different doses of AEJf (62.5–500 mg/kg bw) for 7 days and on the 8th day, cotton pellets were removed and weighed, dried, and weighed again. Results: The results of the oral administration of AEJf at doses of 62.5, 125, 250, and 500 mg/kg bw to rats showed similar acute anti-inflammatory properties such as aspirin (100 mg/kg bw) on carrageenan (1%), fresh egg albumin, and histamine injection-induced rats’ paw edema. AEJf caused 77.63% (preventive study) and 28.1% (curative study) inhibitions of carrageenan (1%) solution-induced paw edema and 61% (preventive study) and 29.62% (curative study) inhibitions of fresh egg albumin-induced paw edema. AEJf also inhibited histamine-induced edema (1 mg/mL) by 83.67% compared to the control group. AEJf significantly reduced the weight of granuloma tissue elicited by the insertion of sterile cotton pellets from 34.53 to 46.98% for wet cottons and from 45.73 to 59.45% for dry cottons. Conclusion: AEJf possessed anti-inflammatory activity on acute and sub-chronic inflammations in rats.